Evangelical Protestantism, Politics, and the Environment: When and How Do Biblical Beliefs Matter?. Issue 5 (3rd May 2020) - Hempel, Lynn; Smith, E. Keith
Abstract: Literature on environment-related outcomes highlights the role of political and religious factors—in particular, political orientation, party affiliation and biblical beliefs. Less is known about how these factors independently and interactively shape attitudes towards policy and environmental behaviors including how political factors may be moderated by religious beliefs. Using structural equation modeling and data from the 2010 GSS, we find that in the United States political orientation and party affiliation independently affect willingness to pay for the environment and to engage in pro-environmental behaviors. Biblical beliefs have no effect on behaviors, but strongly influence willingness to pay. Moreover, biblical beliefs moderate the effects of political orientation: the more politically conservative biblical literalist are the more willing they are willing to pay for the environment. We conclude with a discussion of these surprising results by calling for more intersectional approaches to environment-related behaviors and attitudes.